2020
DOI: 10.1001/jamainternmed.2020.2790
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plant and Animal Protein Intake and Overall and Cause-Specific Mortality

Abstract: IMPORTANCE Although emphasis has recently been placed on the importance of high-protein diets to overall health, a comprehensive analysis of long-term cause-specific mortality in association with the intake of plant protein and animal protein has not been reported.OBJECTIVE To examine the associations between overall mortality and cause-specific mortality and plant protein intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 47 publications
7
138
4
6
Order By: Relevance
“…ARDS is a well-known risk factor for VAP [ 7 , 8 ], and its incidence in mechanically ventilated patients with SARS-CoV-2 pneumonia was reported to be as high as 42–89% [ 1 , 9 ]. In addition, immunosuppressive agents are commonly used in patients with SARS-CoV-2 infection [ 1 ], and SARS-CoV-2 is responsible for altered immune response [ 10 12 ]. However, based on the scarce available data, the incidence of hospital-acquired infections (HAI) appears to be low (13.5%) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…ARDS is a well-known risk factor for VAP [ 7 , 8 ], and its incidence in mechanically ventilated patients with SARS-CoV-2 pneumonia was reported to be as high as 42–89% [ 1 , 9 ]. In addition, immunosuppressive agents are commonly used in patients with SARS-CoV-2 infection [ 1 ], and SARS-CoV-2 is responsible for altered immune response [ 10 12 ]. However, based on the scarce available data, the incidence of hospital-acquired infections (HAI) appears to be low (13.5%) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…den Begriff des Zytokinsturms bei COVID-19 in Frage, da die selbst bei schweren COVID-19-Fällen beschriebenen IL-6-Spiegel zwar deutlich erhöht sind, jedoch weit unter jenen liegen, die sonst bei Non-COVID-19-ARDS oder anderen mit einem Zytokinsturm einhergehenden Entitäten beschrieben werden. Die bei COVID-19 vorliegende systemische Inflammation dürfte sich somit von derjenigen bei anderen Krankheitsbildern wie Sepsis, ARDS oder dem durch CAR-T-Zellen induzierten „cytokine release syndrome“ unterscheiden, was wichtige therapeutische Implikationen mit sich bringt [ 28 , 34 , 40 ].…”
Section: Schwere Verläufe Durch Hyperinflammationunclassified
“…Sources of animal- vs. plant-based proteins and high quality low or high fat, low or high carbohydrate consumption, and quality of overall diet need to be specified more precisely in study designs. Large cohort studies have shown that long-term consumption of plant-based (as compared to animal-based) protein is associated with lower all-cause and cardiovascular disease mortality ( 68 , 69 ). The associations of low-carbohydrate diets (LCDs) and low-fat diets (LFDs) with mortality may depend on the quality and food sources of macronutrients rather than the carbohydrate or fat proportionate content alone ( 70 ).…”
Section: Lifestyle Medicine Domain-specific Findings and Recommendatimentioning
confidence: 99%